Evaluation of in vitro solar protection factor (SPF), antioxidant activity, and cell viability of mixed vegetable extracts from Dirmophandra mollis benth, Ginkgo biloba L., Ruta graveolens L., and Vitis vinífera L. - Cefali, Letícia Caramori (2019)
The aim of this study was to validate a HPLC method for the assay of flavonoids in extracts obtained from natural sources, i.e., from Dirmophandra mollis Benth, Ginkgo biloba L., Ruta graveolens L., and Vitis vinífera L. The potential sun protecting effect, antioxidant activity, and cell viability of the extracts were also determined. Individual extracts (obtained from each individual species) and a mixed extract (containing the four extracts) were analyzed by the validated HPLC method for the identification of flavonoids and quantification of rutin and quercetin. An in vitro cell viability study was carried out using the neutral red method. The in vitro sun protection factor was determined by spectral transmittance and in vitro antioxidant efficacy was evaluated against DPPH, ABTS, and AAPH radicals. The HPLC method used for the identification and quantification of flavonoids in extracts exhibited linearity, precision, accuracy, and robustness. Detection and quantification limits were, respectively, 2.881 ± 0.9 g·mL1 and 0.864 ± 0.9 g·mL1 for quercetin, and 30.09 ± 1 g·mL1 and 9.027 ± 1.1 g·mL1 for rutin. All extracts did not affect cell viability at the evaluated concentration range and exhibited a sun protection effect and antioxidant activity. Among the evaluated extracts, Ginkgo biloba L. and the mixed extract depicted the most expressive antioxidant activity. The mixed extract exhibited sunscreen protection against ultraviolet A (UVA) and ultraviolet B (UVB) and a critical wavelength of 372.7 ± 0.1. Our results translate the enhanced flavonoids composition of the mixed extract, which may be a potential alternative over sunscreens and antioxidants in pharmaceutic/cosmetic formulations.